Geopolymer Concrete Using Fly Ash - Sarker, Prabir; Rangan, Vijaya (Nova Science Publications Inc., 2014)
A summary of the extensive studies conducted on geopolymer concrete is presented; most of the Chapter is devoted to fly ash-based geopolymer concrete. The effects of factors that influence the properties of the geopolymer concrete in the fresh and hardened states are discussed. The properties include compressive strength, tensile strength, modulus of elasticity, drying shrinkage, creep, resistance to sulfate and acid, and fire resistance. The last part of the Chapter describes the behavior of large-scale reinforced geopolymer concrete members and illustrates the application of the geopolymer concrete in the construction industry. Suitability of the available Standards and Codes for design of fly ash based geopolymer concrete beams and columns are presented. Some more recent studies on geopolymers and the economic merits of the geopolymer concrete are also included.